SOCIAL NORMS AND WHISTLEBLOWING INTENTIONS IN DIGITAL FRAUD REPORTING PLATFORMS - Rita J D Atarwaman; Arifuddin Arifuddin; Mediaty Mediaty (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2026)
This study aims to examine the role of social norms in shaping whistleblowing intentions in the use of digital fraud reporting platforms. With the increasing adoption of digital technology in fraud reporting systems, understanding the behavioral factors that influence individuals' willingness to report violations is becoming increasingly important. Social norms, both descriptive and injunctive, play a significant role in influencing individuals' perceptions of environmental support, social risk, and the legitimacy of whistleblowing. This study uses a literature review method by examining scientific articles, academic books, and relevant publications that discuss the relationship between social norms, whistleblowing intentions, and the characteristics of digital fraud reporting platforms. The results of the study indicate that social norms that support organizational transparency, ethics, and accountability tend to increase individuals' intentions to whistleblow through digital platforms. In addition, anonymity, data security, and trust in digital systems interact with social norms to strengthen or weaken reporting intentions. This study confirms that the successful implementation of digital whistleblowing platforms depends not only on technological aspects but also on the social and cultural context of the organization that shapes individual behavior. This research is expected to provide theoretical contributions to the development of behavior-based whistleblowing literature, as well as practical implications for organizations and policymakers in designing effective digital reporting systems oriented toward strengthening positive social norms.